2006
DOI: 10.1016/j.febslet.2006.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the venom proteome of the Colubridae snake Philodryas olfersii revealed from a Duvernoy's (venom) gland transcriptome

Abstract: We investigated the putative toxins of Philodryas olfersii (Colubridae), a representative of a family of snakes neglected in venom studies despite their growing medical importance. Transcriptomic data of the venom gland complemented by proteomic analysis of the gland secretion revealed the presence of major toxin classes from the Viperidae family, including serine proteases, metalloproteases, C-type lectins, Crisps, and a C-type natriuretic peptide (CNP). Interestingly, the phylogenetic analysis of the CNP pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 28 publications
8
91
2
1
Order By: Relevance
“…expected from published data, B. arietans venom protein contains antigenic epitopes recognized by antibodies generated by non-Viperidae snake venoms (Junqueirade-Azevedo and Ho, 2002;Guo et al, 2007;Ching et al, 2006). In fact, in this study, we experimentally demonstrated that the isolated 50-kDa protein was recognized by antibodies present in horse polyclonal F(ab´) 2 or in chicken IgY anti-Bitis arietans, anti-Bitis spp., anti-Naja spp., anti-Lachesis muta, anti-Bothrops spp., and antiCrotalus spp.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…expected from published data, B. arietans venom protein contains antigenic epitopes recognized by antibodies generated by non-Viperidae snake venoms (Junqueirade-Azevedo and Ho, 2002;Guo et al, 2007;Ching et al, 2006). In fact, in this study, we experimentally demonstrated that the isolated 50-kDa protein was recognized by antibodies present in horse polyclonal F(ab´) 2 or in chicken IgY anti-Bitis arietans, anti-Bitis spp., anti-Naja spp., anti-Lachesis muta, anti-Bothrops spp., and antiCrotalus spp.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies indicate that SVMPs and ADAMs are involved in hemorrhage, edema, hypotension, inflammation and necrosis induced by snake venoms (Gutiérrez and Rucovaldo, 2000). Although Viperidae snake venoms are rich in SVMPs, these enzymes have also been observed in certain Elapidae and Colubridae venoms (Junqueira-de-Azevedo and Ho, 2002;Guo et al, 2007;Ching et al 2006). SVMPs act by cleaving proteins on the vascular basement membrane and surrounding connective tissues as well as by altering platelet structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the lack of atrial natriuretic peptide in the reptile physiology (29), the lizard venom types were nested within the BNP clade. In contrast, as reported previously (30), the snake forms were all nested within the CNP clade (Fig. 7).…”
Section: Resultscontrasting
confidence: 52%
“…13). The homomeric and the heterodimeric lectin forms had been considered previously to be the result of two separate toxin recruitment events (3) or the result of a single recruitment event (18). However, reconstructing the evolutionary history had been hampered by the scarcity of homomeric sequences.…”
Section: Evolution Of An Arsenalmentioning
confidence: 99%